Spatial data-based closure costing integrated with life of mine planning: a key enabler facilitating value realisation - Kumari, P; Cooper, M (Mine Closure 2019: Proceedings of the 13th International Conference on Mine Closure, 2019)
Knowing with reasonable accuracy the life-of-mine (LoM) closure cost estimate at the initial stages for operating mines can significantly help with efficient operational planning and ensure a sustainable closure—a key principle of integrated mine closure planning. The conventional, quantity surveying-based closure costing methods work reasonably well for infrastructure demolition costs compared with the landform design costs. Utilising spatial data modelling tools that allow for an accurate quantification of material movement volumes is an attractive improvement on the existing methods. Spatial models can be built to calculate closure costs from first principles. This provides a clear understanding of significant cost categories and the underlying cost drivers, resulting in accurate cost estimates. In addition, these models enable users with an efficient way of comparing multiple landform designs for any given optimisation criteria (e.g. legal, regulatory, environmental and financial constraints). Coupled with the resource management and scheduling modules, the tool enables direct integration of closure planning into the LoM planning and provides detailed LoM schedules and cash flow. Easy opportunity and risk analyses of various planning options assist in designing an optimised concurrent rehabilitation cash flow over the operational LoM, ensuring that the residual liability at the end of the life is minimal when the mine profits would usually decline. This paper presents a case study of a large open pit hard rock mining operation, the Anglo American-owned Mogalakwena platinum mine in South Africa, where the closure cost estimate was significantly improved in accuracy when using a digital terrain model (DTM) in a Deswik closure costing platform (Enviro tool and modules). Built from first principles and with detailed resource allocations (incorporating equipment/labour efficiencies and schedules), the 3D costing model highlighted that reshaping of certain waste rock dump slopes into final landform would have significant material movement costs due to constrained dumping space at the mine—enabling the mine to consider a revised LoM waste placement strategy and concurrent rehabilitation plan. This paper also discusses the challenges in establishing a flexible and robust 3D costing model, and shares learnings from the Mogalakwena project.
Keywords: closure cost